Impact of glgA1, glgA2 or glgC overexpression on growth and glycogen production in Synechocystis sp. PCC 6803 - Mittermair, Sandra; Lakatos, Gergely; Nicoletti, Cecilia; Ranglová, Karolína; Manoel, João Câmara; Grivalský, Tomáš; Kozhan, Daniyar Malikuly; Masojídek, Jiří; Richter, Juliane (Journal of biotechnology, 2021)
Low production rates are still one limiting factor for the industrial climate-neutral production of biovaluable compounds in cyanobacteria. Next to optimized cultivation conditions, new production strategies are required. Hence, the use of established molecular tools could lead to increased product yields in the cyanobacterial model organism Synechocystis sp. PCC6803. Its main storage compound glycogen was chosen to be increased by the use of these tools. In this study, the three genes glgC, glgA1 and glgA2, which are part of the glycogen synthesis pathway, were combined with the Pcpc560 promoter and the neutral cloning site NSC1. The complete genome integration, protein formation, biomass production and glycogen accumulation were determined to select the most productive transformants. The overexpression of glgA2 did not increase the biomass or glycogen production in short-term trials compared to the other two genes but caused transformants death in long-term trials. The transformants glgA1_11 and glgC_2 showed significantly increased biomass (1.6-fold - 1.7-fold) and glycogen production (3.5-fold - 4-fold) compared to the wild type after 96 h making them a promising energy source for further applications. Those could include for example a two-stage production process, with first energy production (glycogen) and second increased product formation (e.g. ethanol).
Keywords: Glycogen; glykogen; Synechocystis